Susceptibility and Virulence of Enterobacteriaceae Isolated from Urinary Tract Infections in Benin - Funkè F. Assouma; Haziz Sina; Tomabu Adjobimey; Agossou Damien Pacôme Noumavo; Akim Socohou; Bawa Boya; Ange D. Dossou; Lauriane Akpovo; Basile Boni Saka Konmy; Jacques F. Mavoungou; Adolphe Adjanohoun; Lamine Baba-Moussa (Microorganisms, 2023)
Enterobacteriaceae represent one of the main families of Gram-negative bacilli responsible for serious urinary tract infections (UTIs). The present study aimed to define the resistance profile and the virulence of Enterobacteriaceae strains isolated in urinary tract infections in Benin. A total of 390 urine samples were collected from patients with UTIs, and Enterobacteriaceae strains were isolated according to standard microbiology methods. The API 20E gallery was used for biochemical identification. All the isolated strains were subjected to antimicrobial susceptibility testing using the disc diffusion method. Extended-spectrum beta-lactamase (ESBL) production was investigated using a double-disc synergy test (DDST), and biofilm production was quantified using the microplate method. Multiplex PCR was used to detect uro-virulence genes, namely: PapG, IronB, Sfa, iucD, Hly, FocG, Sat, FyuA and Cnf, using commercially designed primers. More than 26% (103/390) of our samples were contaminated by Enterobacteriaceae strains at different levels. Thus, E. coli (31.07%, 32/103), Serratia marcescens (11.65%, 12/103), Klebsiella ornithinolytica (8.74%, 9/103), Serratia fonticola (7.77%, 8/103) and Enterobacter cloacae (6.80%, 7/103) were identified. Among the isolated strains, 39.81% (41/103) were biofilm-forming, while 5.83% (6/103) were ESBL-producing. Isolates were most resistant to erythromycin, cefixime, ceftriaxone and ampicillin (≥90%) followed by ciprofloxacin, gentamycin, doxycycline and levofloxacin (≥50%), and least resistant to imipenem (27.18%). In regard to virulence genes, Sfa was the most detected (28.15%), followed by IronB (22.23%), iucD (21.36%), Cnf (15.53%), PapG (9.71%), FocG (8.74%), Sat (6.79%), FyuA (5.82%) and Hyl (2.91%). These data may help improve the diagnosis of uropathogenic strains of Enterobacteriaceae, but also in designing effective strategies and measures for the prevention and management of severe, recurrent, or complicated urinary tract infections in Benin.